(untitled) (Analele Universității București.Filosofie, 2025)
In this paper, I aim to evaluate the meaning of Gregory Palamas’ ontology of the self in the context of the semantic itinerancy between Plotinus, the first one to propose the ontological dimension of the self, and the patristic horizon. I will survey the semantic re-semanticization of terms that can be found from Plotinus to the fourteenth century, the time of Gregory Palamas’ anthropological perspective. The corresponding concepts in modern languages have accumulated connotations linked to the horizon of modernity, resulting in semantic alterations or alienations. This confusing interpretative approach is linked, no less, to paradigms of modern sources, as in the case of understanding the Neoplatonic self on the scheme of Cartesian dualism.